2023
DOI: 10.1002/iid3.945
|View full text |Cite
|
Sign up to set email alerts
|

GAS5 silencing attenuates hypoxia‐induced cardiomyocytes injury by targeting miR‐21/PTEN

Abstract: Introduction Myocardial hypoxia is an important factor causing myocardial infarction (MI). Interestingly, many unknown factors in the molecular mechanism of MI remain unclear. Our study explored the role of lncRNA growth arrest‐specific 5 (GAS5) in cell injury under hypoxia. Methods AS5 expression was assessed in MI and human cardiomyocytes under hypoxia through RT‐qPCR assay. Methyl thiazolyl tetrazolium assay, flow cytometry assay, and transwell assay was carried out for cell viability, cell apoptosis, cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…These regulatory roles of lncRNAs have important implications for the development and progression of HF [ 50 ]. For example, antisense lncRNA Kcna2 (Long non-coding RNA Potassium Voltage-Gated Channel Subfamily A Member 2) is linked to a higher prevalence of ventricular arrhythmias, which are irregular heartbeats that only impact the heart’s lower chambers in heart failure patients [ 51 ]. The study found that Kcna2 knockdown in the heart decreased the slow component of the rectifier potassium current (IKs) and prolonged action potentials in cardiomyocytes, consistent with the changes observed in heart failure.…”
Section: Unraveling the Role Of Lncrnas In Heart Disease Pathogenesismentioning
confidence: 99%
See 4 more Smart Citations
“…These regulatory roles of lncRNAs have important implications for the development and progression of HF [ 50 ]. For example, antisense lncRNA Kcna2 (Long non-coding RNA Potassium Voltage-Gated Channel Subfamily A Member 2) is linked to a higher prevalence of ventricular arrhythmias, which are irregular heartbeats that only impact the heart’s lower chambers in heart failure patients [ 51 ]. The study found that Kcna2 knockdown in the heart decreased the slow component of the rectifier potassium current (IKs) and prolonged action potentials in cardiomyocytes, consistent with the changes observed in heart failure.…”
Section: Unraveling the Role Of Lncrnas In Heart Disease Pathogenesismentioning
confidence: 99%
“…Conversely, Kcna2 overexpression in the heart significantly attenuated the CHF-induced decreases in the IKs, AP prolongation, and ventricular arrhythmias. This discovery highlights the role of lncRNAs in cardiac electrical remodeling and the development of arrhythmias in heart failure [ 51 ]. Additionally, lncRNA UCA1 (Long non-coding RNA urothelial carcinoma-associated 1) has been shown to promote the progression of cardiac hypertrophy, a condition commonly associated with various cardiovascular diseases such as heart failure.…”
Section: Unraveling the Role Of Lncrnas In Heart Disease Pathogenesismentioning
confidence: 99%
See 3 more Smart Citations